2023
DOI: 10.1021/acschemneuro.2c00668
|View full text |Cite
|
Sign up to set email alerts
|

Plantamajoside Alleviates Substantia Nigra Damage in Parkinson’s Disease Mice by Inhibiting HDAC2/MAPK Signaling and Reducing Microglia Polarization

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder caused by dopaminergic neuron progressive degeneration. Inhibition of microglial activation may contribute to the treatment and prevention of PD. Plantamajoside (PMS) is a natural compound extracted from plantain seeds. It has a wide range of biological activities, including anti-inflammatory, antioxidative, as well as antitumor effects. However, its possible effects on PD are still unclear. In this study, lipopolysaccharide (LPS) was first inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Exenatide treatment of SNCA neurons led to significant suppression of MAPK pathway kinases JNK and p38. JNK signalling is activated in response to inflammatory stimuli, and has been found to be elevated in postmortem PD brains 65 , whereas pharmacological inhibition of JNK by GLP-1R agonists is protective in animal models of PD 59 , and a number of studies indicate degeneration of nigral dopaminergic neurons is accompanied by an increase in the level of p38 MAPKs 67,68 , while pharmacological inhibition of p38MAPK prevents toxin-induced apoptosis in PD models [69][70][71][72] .…”
Section: Discussionmentioning
confidence: 99%
“…Exenatide treatment of SNCA neurons led to significant suppression of MAPK pathway kinases JNK and p38. JNK signalling is activated in response to inflammatory stimuli, and has been found to be elevated in postmortem PD brains 65 , whereas pharmacological inhibition of JNK by GLP-1R agonists is protective in animal models of PD 59 , and a number of studies indicate degeneration of nigral dopaminergic neurons is accompanied by an increase in the level of p38 MAPKs 67,68 , while pharmacological inhibition of p38MAPK prevents toxin-induced apoptosis in PD models [69][70][71][72] .…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation revealed that Plantamajoside exerted its effects in both PD mice and BV-2 cells by suppressing the activation of the histone deacetylase-2 (HDAC2)/MAPK pathway. Notably, Plantamajoside demonstrated its ability to reduce microglia polarization by inhibiting HDAC2 ( Guo et al, 2023 ).…”
Section: Neurodegenerative Diseases Involving Microglia (M1/m2) Pathwaymentioning
confidence: 99%